Avaliação de equipamentos de aplicação de herbicidas em operação de repasse em cana-de-açúcar e segurança para o trabalhador - Machado Neto, J.G. [UNESP]; Machado, R.F. [UNESP] (Sociedade Brasileira da Ciência das Plantas Daninhas, 2007)
Objetivou-se com este trabalho classificar em seguras ou inseguras as condições de trabalho de aplicação da formulação comercial de paraquat a 0,5% e de abastecimento dos tanques em operação de repasse em cultura de cana-de-açúcar com os pulverizadores costal manual, costal pressurizado e Pulmipur manual; determinar o efeito das variações na operação de repasse em quatro usinas de açúcar e álcool com o pulverizador costal pressurizado sobre as exposições dos trabalhadores ao paraquat; determinar a eficácia de equipamentos de proteção individual nessas condições de trabalho; e avaliar a intensidade da deriva e a eficácia de acessórios protetores de deriva. As exposições dérmicas e respiratórias dos trabalhadores foram avaliadas e utilizadas para calcular a margem de segurança (MS). Os valores de MS foram utilizados para classificar essas condições de trabalho em seguras (MS > 1) ou em inseguras (MS < 1). Para avaliar a deriva das aplicações na cultura e a eficácia dos protetores de deriva, foram estudados os tratamentos: formulação comercial de paraquat a 0,5% na calda, aplicada com o costal manual, sem e com o chapéu de proteção de deriva; com o costal pressurizado, sem e com a planilha de proteção de deriva; formulação comercial de paraquat pura com o Pulmipur; formulação comercial de glyphosate a 1% com o costal pressurizado e com a planilha, e puro com o Pulmipur; e testemunha sem aplicação. As duas atividades com o Pulmipur proporcionam as maiores exposições dérmicas, devido ao manuseio da formulação, e são inseguras sem o uso dos EPIs e seguras com estes. As atividades com o pulverizador costal manual ou pressurizado são seguras com ou sem os EPIs. As grandes diferenças nas EDs dos trabalhadores se devem às diferenças no tempo de trabalho diário e no número de trabalhadores nas equipes entre as usinas de açúcar e álcool. O protetor de deriva tipo chapéu é eficaz no controle da deriva na aplicação do paraquat, e a planilha, não.

The aims of this study were to classify as safe or unsafe the work conditions under which a commercial formulation of paraquat at 0.5% was applied and the loading tanks used for post-emergence weed control of a sugar cane crop, using a hand -held, pressurized sprayer or Pulmipur hand-held backpack sprayer; to determine the effect of variations in herbicide application at four Sugar and Alcohol Plants using a pressurized backpack sprayer on worker exposure to paraquat ; to assess the efficacy of personal protective equipments (PPEs) under these work conditions; and to evaluate the extent of drift and PPE efficacy against drift. Dermal and respiratory exposure of the workers was determined and used to calculate the margin of safety (MOS). The MOS values were utilized to classify these work conditions as safe (MOS e 1) or unsafe (MOS < 1). To evaluate the drift resulting from application on the crops and the efficacy of protective gear against it, the following treatments were studied: a commercial formulation of paraquat at 0.5% in the spray mix, applied with the hand-held backpack sprayer, with and without protective hat against drift, and with pressurized backpack sprayer, with and without protective shield against drift; a commercial formulation of pure paraquat with Pulmipur; a commercial formulation of glyphosate at 1% (utilized as standard treatment for comparison) applied with the pressurized backpack sprayer and shield, and pure glyphosate with Pulmipur; and control without application. The two activities with Pulmipur produced the greatest dermal exposures due to formulation handling and were considered unsafe without the use of PPEs and safe with the PPEs. The activities using hand-held or pressurized backpack sprayer were safe with or without PPEs. The great differences in the dermal exposures of the workers were due to the differences in daily work time and number of workers in the teams of the Sugar and Alcohol Plants. The hat type protective gear against drift was effective under paraquat application whereas the shield was not.
Evaluation of herbicide application using backpack sprayers for post-emergence weed control in sugar cane crop and safe work conditions
Keywords: Sugarcane; drift control; personal protective equipment-PPEs; occupational intoxication risk; work safety; Cana-de-açúcar; controle de deriva; equipamentos de proteção individual - EPIs; risco de intoxicação; segurança no trabalho